2010
DOI: 10.1108/07378831011026724
|View full text |Cite
|
Sign up to set email alerts
|

Interoperability of open access repositories in computer science and IT – an evaluation

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:448207 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…A number of studies have focused on IRs in specific geographical areas, such as Canada (Shearer, 2006), Zimbabwe (Nyambi & Maynard, 2012), India (Sawant, 2011;Tripathi & Jeevan, 2011), or Asian countries in general (Nazim & Mukherjee, 2011). Other focuses have been on subjectbased repositories for particular disciplines, such as chemistry (Warr, 2003) and computer science and IT (Bhat, 2010). There is also a significant amount of literature on format repositories, particularly repositories for theses (an overview has been provided by Yiotis, 2008) and learning objects (a quantitative study of the global infrastructure is provided by Ochoa and Duval, 2009).…”
Section: Research Contextmentioning
confidence: 99%
“…A number of studies have focused on IRs in specific geographical areas, such as Canada (Shearer, 2006), Zimbabwe (Nyambi & Maynard, 2012), India (Sawant, 2011;Tripathi & Jeevan, 2011), or Asian countries in general (Nazim & Mukherjee, 2011). Other focuses have been on subjectbased repositories for particular disciplines, such as chemistry (Warr, 2003) and computer science and IT (Bhat, 2010). There is also a significant amount of literature on format repositories, particularly repositories for theses (an overview has been provided by Yiotis, 2008) and learning objects (a quantitative study of the global infrastructure is provided by Ochoa and Duval, 2009).…”
Section: Research Contextmentioning
confidence: 99%
“…In terms of non-journal documents, Bhat found that OAIster retrieved 73% of documents from the ten OAI-PMH compliant repositories in their study; however, OAIster ranked eighth behind general-purpose search engines including Google, suggesting that OAIster is succeeding but that harvestable repositories still have more work to do with respect to improving their visibility in OAIster and other discovery tools. 23 While these "alternative uses" of OAIster are significant, the remainder of this review will evaluate OAIster as a tool for library end users to discover and access relevant information. Three interfaces will be reviewed: the public interface to OAIster, WorldCat.org; the First-Search interfaces, and EBSCO Discovery Service (EDS).…”
Section: Pricing: N/a N/a N/a Contract Options: N/a N/a N/amentioning
confidence: 99%
“…Visibility can be enhanced by putting research into IRs that are OAI-PMH interoperable. 5 The OAI-PMH protocol was primarily developed as a low-barrier method for interoperability between metadata repositories and provides an interoperability framework based on metadata harvesting by defining two classes of participants: data providers that expose metadata and service providers that harvest metadata. The IR's metadata schema has a key role in increasing interoperability of the repository, i.e., maximizing visibility of theses and dissertations that are stored in the repository.…”
Section: Literature Reviewmentioning
confidence: 99%